Student Attitudes toward Learning Analytics in Higher Education: “The Fitbit Version of the Learning World” - Roberts, Lynne D.; Howell, Joel A.; Seaman, Kristen; Gibson, David C. (Frontiers in Psychology, 2016)
Increasingly, higher education institutions are exploring the potential of learning analytics to predict student retention, understand learning behaviours, and improve student learning through providing personalised feedback and support. The technical development of learning analytics has outpaced consideration of ethical issues surrounding their use. Of particular concern is the absence of the student voice in decision-making about learning analytics. We explored higher education students’ knowledge, attitudes and concerns about big data and learning analytics through four focus groups (N=41). Thematic analysis of the focus group transcripts identified six key themes. The first theme, ‘Uninformed and Uncertain’, represents students’ lack of knowledge about learning analytics prior to the focus groups. Following the provision of information, viewing of videos and discussion of learning analytics scenarios three further themes; ‘Help or Hindrance to Learning’, ‘More than a Number’, and ‘Impeding Independence’; represented students’ perceptions of the likely impact of learning analytics on their learning. ‘Driving Inequality’ and ‘Where Will it Stop?” represent ethical concerns raised by the students about the potential for inequity, bias and invasion of privacy and the need for informed consent. A key tension to emerge was how ‘personal’ versus ‘collective’ purposes or principles can intersect with ‘uniform’ versus ‘autonomous’ activity. The findings highlight the need the need to engage students in the decision making process about learning analytics.